Editorial [Hot topic: Neuroprotection in ALS: From Pathology to Treatment (Guest Editors: Gabriele Siciliano and Luigi Murri)] - Murri, Luigi (CNS & Neurological Disorders - Drug Targets, 2010)
These past years have seen the publication of numerous scientific articles and books on amyotrophic lateral sclerosis (ALS) that probably reflect the great human and social impact of this devastating disease on affected patients and relatives. It is common to define ALS as a “treatable”, although “far from being curable”, disorder. Multidisciplinary teams in specialized ALS centers are looking to identify reliable pathogenic markers of the disease, both in familial and sporadic cases, in attempts to design effective therapies capable of slowing down the loss of cortical, brainstem, and spinal cord motor neurons. This “Hot Topic” issue entitled “Neuroprotection in Amyotrophic Lateral Sclerosis: From Pathology to Treatment”, edited by Gabriele Siciliano and Francesco Fornai and focused on a recent ad hoc meeting held in Pisa in September 2009, gathers the most recent knowledge on a fundamental topic that has been the target of a number of basic and applied research strategies in the last decade. This issue comprehensively covers the main aspects related to the mechanisms and pathways leading to neurodegeneration in ALS, while the contributing authors clearly track possible developments of the more recent experimental acquisitions in terms of planning therapeutic approaches that could be valuable for a pathogenic treatment of this disease. Topics such as experimental models of ALS, cell culture and animal models, and mechanisms of motor neuron degeneration such as autophagy, histone deacetylation, protein aggregation and defective RNA metabolism, glutamate excitotoxicity and oxidative stress, are treated in a perspective which seeks to report what significantly can be translated from basic research to promising clinical application, ranging from neuro-protective drugs to stem cell therapy. The establishment of a relationship between “a factor and the disease” can be an important step in unraveling some of ALS's mystery and might be utilized to develop more appropriate experimental designs and targeted clinical trials.